THE EFFECT OF LIQUIDITY, LEVERAGE, AND PROFITABILITY ON THE FINANCIAL PERFORMANCE OF AGRICULTURAL COMPANIES - Lisa, Dea; Suhardi (Kajian Akuntansi, 2025)
Abstract. The purpose of this study is to examine how the financial performance of agricultural sector companies listed on the Indonesia Stock Exchange (IDX) between 2020 and 2024 is impacted by liquidity, leverage, and profitability. Return on Equity (ROE) is the dependent variable used to measure financial performance, while Current Ratio (CR), Debt-to-Equity Ratio (DER), and Return on Assets (ROA) are the independent variables used to measure liquidity, leverage, and profitability. Using secondary data from 24 businesses over a five-year period of observation, panel data regression with the Fixed Effect Model (FEM) approach is the analysis technique employed. The findings demonstrated that ROA has a positive and significant impact on ROE, whereas DER has a negative and significant impact. In the meantime, ROE is not significantly impacted by CR. With an R-squared value of 0.6922, which indicates that 69.22 percent of ROE variation can be explained by CR and DER, the three independent variables simultaneously have a significant impact on financial performance.